Relationship between the presence of metabolic syndrome and electrocardiographic abnormalities in HIV patients with HAART in a level III hospital, Lima - Peru - Taza Caroy, Jaime Enzo (2021)
Introduction: Antiretroviral Therapy (ARVT) has been related to some elements of Metabolic Syndrome (MS). Likewise, there exists a high prevalence of alterations on the electrocardiogram (ECG) in people with HIV. Objective: Evaluate the association between MS and alterations in the ECG in HIV patients who received ARVT. Methodology: A consecutive non-randomized cross-sectional study was developed in which patients from the Infectious Disease Service of the Arzobispo Loayza National Hospital were evaluated from January 2019 to April 2020. Survey data, clinical history, clinical examination and a 12-lead ECG were performed to each participant. Alterations in the ECG were classified with the Minnesota code. For SM, NCEP-ATP III 2005 criteria was used. Results: 63 patients were included, the mean age was 38,78 years (SD: 9,23). 25 participants presented electrocardiographic alteration, being 24 minor alterations and 5 major alterations. 27 from the 63 patients (42,9%) had MS. Association was found between MS and ECG alterations in the adjusted model by sex, age, smoking, time with HIV, time with ARVT and use of another medication, with a relative prevalence (RP) value of 2,17 (IC=95% 1,21-3,90) (p=0,009). Conclusion: Although association between the presence of MS and ECG alterations in the HIV population was found, due to the low power of the study, it is recommended to manage the results with caution.